Characterization and Evaluation of Antidiabetic Potentials of Plectranthus amboinicous-Derived Nanoparticles - MH, Shaeena; D.R, Bharathi (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Plectranthus amboinicus (Lour.) Spreng, a member of the Lamiaceae family, is commonly utilized in both traditional medicine and culinary applications. This research focuses on optimizing the pharmacodynamic and pharmacokinetic characteristics of Plectranthus amboinicus by developing and assessing a nanoparticle formulation combined with gelatin. The objective was to evaluate the effectiveness of this nanoformulation in enhancing glucose metabolism and its potential as an antidiabetic agent. Materials and Methods The nanoparticle formulation of Plectranthus amboinicus was developed using gelatin as the carrier via the solvent evaporation method. The resulting nanoparticles were roughly 250 nm in diameter and exhibited a spherical morphology. Toxicity tests were conducted at concentrations up to 1000 μg/mL. The potential antidiabetic effects were evaluated by measuring glucose uptake in 3T3-L1 adipocytes and L6 myoblast cells. Results The gelatin-conjugated nanoparticles of Plectranthus amboinicus were non-toxic at concentrations up to 1000 μg/mL. They significantly improved glucose uptake in L6 myoblast cells, indicating better glucose metabolism. Additionally, the formulation showed promise in decreasing fat accumulation and carbohydrate digestion, implying significant antidiabetic effects. Conclusion The Gelatin-conjugated Plectranthus amboinicus Nanoparticles (GPAN) show promise for enhancing glucose metabolism and offering antidiabetic benefits. This study highlights GPAN as a promising candidate for further investigation and development due to its effectiveness in improving glucose uptake and its favorable safety profile. This positions GPAN as a potential therapeutic option for diabetes and other related metabolic disorders.
Keywords: Spherical; Glucose; Preadipocytes; Nanotechnology; Therapies; Solvent Evaporation.